Effects of Retinol, Natural Pea Peptide and Antioxidant Blend in a Topical Formulation: In Vitro and Clinical Evidence - Brian Cook; Melanie Riggs; K. C. Holley; Helen Knaggs; Ganesh Diwakar; Edwin D. Lephart (Dermatology and Therapy)
Abstract Introduction Retinol has a long history of treating skin conditions, including photoaging. However, skin irritation with repeated use of retinol is well documented. The present study assessed the effectiveness of a novel topical formulation, referred to as retinol topical formulation (RTF), to improve the quality of skin health. The RTF was composed of a low dose retinol, a synthetic retinoid ester, a pea peptide, and an antioxidant blend. Methods In vitro assessment of RTF on human skin co-cultures (human keratinocytes, melanocytes, and dermal fibroblasts) identified gene expression levels and skin biomarkers after 24 h exposure. An 8-week clinical study was conducted to evaluate once-nightly application of the RTF for short-term and long-term benefits in 30 adult subjects between 35 and 70 years of age (21 female, 9 male). Skin evaluations were conducted via bioinstrumentation (for hydration, transepidermal water loss and elasticity) and at 0, 1-, 2-, 4-, and 8-week self-assessment questionnaires and photo-imaging analysis were performed. Results RTF treatment of skin in vitro co-cultures upregulated aquaporin-3, PER1, collagen, and elastin, and downregulated expression of MMP1 and the pigmentation genes TYRP1 and MITF. The clinical assessment significantly improved hydration, transepidermal water loss, and elasticity along with incremental but significant increases in nine skin parameters (hydration, clarity, radiance/glow, smoothness, brightness, texture, appearance of pores, dark spots/hyperpigmentation, and skin tone evenness from baseline) with continuous use over 8 weeks compared to baseline values. Conclusions The RTF in vitro analysis showed significant positive changes for several skin biomarkers, and the clinical assessment showed RTF significantly improved the visible signs of dermal aging, without irritation.